NUTRIENT CYCLING IN DIFFERENT SUCCESSIONAL STAGES OF FOREST ATLANTIC, IN RIVER BASIN SUL PARAIBA, RJ - Machado, Deivid Lopes [UNESP]; Pereira, Marcos Gervasio; Fernandes Correia, Maria Elizabeth; Diniz, Anderson Ribeiro; Santos, Lauana Lopes dos; Gabriel Menezes, Carlos Eduardo (Univ Federal Uberlandia, 2015)
In forest ecosystems, the contribution and decomposition of litterfall are the primary means of transferring nutrients to the soil, being of great importance for the sustainability of these systems. However, studies about the influence of succesional stages in the dynamics of nutrient cycling in secondary forests are scarce, especially those located in relief irregular, where are concentrated much of the Atlantic Forest fragments in southeastern Brazil. This work aimed to study the cycling of nutrients in different successional stages of submontane semideciduous seasonal forest, through of monthly and annual litterfall production, by nutrient availability and the rate of decomposition of leaf material. We studied three areas with different successional stages, located in Pinheiral, RJ: forest in initial stage (FIS), forest in intermediate stage (FINS) and forest in advanced stage (FAS). The litter production was evaluated monthly for one year (April/2009 to March/2010) through conical collector 0,21m2. The litter collected was dried and stratified into leaves, branches, and other reproductive materials (fractions unidentifiable) and weighed. Subsequently, the material was homogenized and N, P, K, Ca and Mg concentrations were determined. The decomposition of leaf material was evaluated for 120 days using litter bags. It was found annual litter of 7.47 Mg ha(-1) in FIS, 8.96 Mg ha(-1) in FINS and 14.7 Mg ha(-1) in FAS, with the leaf fraction representing, respectively, 86.4%, 80.7% and 66.1% of the total contributed. Concentration and content of nutrients, in general, were less in FIS, intermediate in FINS and higher in FAS. The litter was shown to be an important route of transfer of N and Ca to the soil, especially N in FAS and Ca in FINS and FEI. The half-life in FAS was 151 days, followed FINS (217 days) and FIS (315 days), observing the FAS greater loss of material throughout the study period. Ours results showed that the successional age affected the total amount of nutrients produced via litter, according to the structural complexity in terms of increase of plant species richness and basal area. Thereby, one can expect that, provided there are favorable conditions such as sources of propagules and dispersers, secondary forest succession in areas of relief irregular and with low fertility soils, condition the formation of a nutritionally sustainable forest.
Keywords: Litterfall; Decomposition; Macronutrients; Forest Succession; Assisted Restoration